Presentation and Management of Cardiac arrhythmias ... an analysis of 75 referrals from Family Medicine Practitioners (University Heart Journal, 2009)
Cardiac arrhythmias often present to family physicians with diverse clinical manifestations. This retrospective observational study was carried out in a private cardiology clinic in Dhaka from July 2004 to December 2008. A total of 1257 patients were referred from family physicians in the locality. 75 (5.96%) patients were diagnosed as having cardiac arrhythmia by ECG. Various types of atrial arrhythmias are more common than ventricular arrhythmias (60% vs 40%). Atrial fibrillation (N=18) and PVC (N=17) are the 2 commonest arrhythmias found in this study. This study identifies the clinical presentation, possible aetiology and management of patients having cardiac arrhythmias. Palpitation (46.66%) and asymptomatic ECG changes (34.66%) were the 2 most common reasons for referral. Most of the patients could be managed on a out-patient basis. Most arrhythmias like 1st degree heart block, PAC & isolated PVC, RBBB, Sinus bradycardia were asymptomatic & did not need any further treatment except assurance & anxiolytics. Other arrhythmias like atrial fibrillation, LBBB, bifascicular or advanced heart block, SSS & SVT needed further evaluation. This article particularly focuses on the general approach of family physicians while dealing with patients with cardiac arrhythmias. Key words: cardiac arrhythmias, family medicine practice   doi: 10.3329/uhj.v5i1.3435 University Heart Journal Vol. 5, No. 1, January 2009 17-19